2010
DOI: 10.1055/s-0030-1262953
|View full text |Cite
|
Sign up to set email alerts
|

The Radial Artery Superficial Palmar Branch Flap: A Modified Free Thenar Flap with Constant Innervation

Abstract: The free thenar flap is useful for coverage of volar finger defects but has an inconstant innervation based on the presence of either the lateral antebrachial cutaneous nerve (LABC) or the superficial sensory branch of the radial nerve (SSRN). A detailed anatomic study on 30 adult fresh frozen cadavers preinjected with silicone rubber compound to demarcate arterial anatomy documented locations, numbers, and diameters of arteries and skin perforators with surrounding nerves. The palmar cutaneous branch of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 19 publications
0
62
1
1
Order By: Relevance
“…However, muscle reinnervation would afford deep sensation and proprioception. Depending upon the nature of the defect and the skin cover incorporated with the reconstruction, it may be possible to direct the reliably present palmar cutaneous branch of the median nerve [15] or other sensory branch towards improved sensory reconstruction. In summary, the anconeus has promising morphological, vascular, and gross motor nerve characteristics that merit its consideration for use as a FFMT in reconstructing select defects of the thenar eminence for which standard reanimation techniques are not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…However, muscle reinnervation would afford deep sensation and proprioception. Depending upon the nature of the defect and the skin cover incorporated with the reconstruction, it may be possible to direct the reliably present palmar cutaneous branch of the median nerve [15] or other sensory branch towards improved sensory reconstruction. In summary, the anconeus has promising morphological, vascular, and gross motor nerve characteristics that merit its consideration for use as a FFMT in reconstructing select defects of the thenar eminence for which standard reanimation techniques are not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported two patients with volar thumb defects that underwent sensory reconstruction using a free thenar flap with a PCBMN. 9 The sensitivity to M2PD in these two patients was more than 15 mm and 6 mm at 5 months after surgery. Sakai also reported two patients who were treated with a free thenar flap to cover the lateral and volar sides of the fingers.…”
Section: Introductionmentioning
confidence: 65%
“…The present variation is very rare condition as it is piercing the flexor retinaculum and running in the carpal tunnel. Knowing the course of superficial palmar branch of radial artery is not only important for its possibility of causing carpal tunnel syndrome but also has importance for reconstructive surgeons as this artery is used as flap for finger reconstruction [7,8].…”
Section: Discussionmentioning
confidence: 99%